Korelasi Kompetensi Guru PAK SMA Negeri Se-Jakarta dengan Identitas sebagai Hamba Tuhan - Jacob Messakh (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
In the midst of the dynamics of intolerance that has penetrated the world of education in Jakarta, especially in the aftermath of the 2017 Jakarta Election, education for all and the ideals of independence attributed to the National Education System Law became a research concern. The focus is on Christian Religious Education Teachers (PAK) who are religious-based educators (religious). The deepening of Master's competence (PAK) is based on 1 Peter by providing background biblical texts as the basis of its epistemology. As a data collection instrument using a questionnaire to a number of 50 PAK Teacher respondents representing 5 regions namely: Central Jakarta, North Jakarta, Jakarta, South, West Jakarta and East Jakarta. The test uses a correlation regression test for each item questionnaire with five answer choices (Likert scale). The results show that there is a positive (unidirectional) relationship between the Competency variables as PAK Teachers and the identity variable as servants of God. With a correlation value of 0.715, it is shown that the correlation between PAK Teacher competency variables with self-identity as a servant of God is not only positive (unidirectional) but also included in the strong category. Abstrak Di tengah dinamika intoleransi yang merambah dunia pendidikan di Jakarta khususnya pasca Pilkada Jakarta 2017 silam, pendidikan untuk semua dan cita-cita kemerdekaan yang diatribusi ke dalam UU Sistem Pendidikan Nasional menjadi perhatian penelitian. Fokusnya adalah Guru Pendidikan Agama Kristen (PAK) yang merupakan pendidik berbasis keagamaan (religius). Pendalaman terhadap kompetensi Guru (PAK) didasarkan kepada Surat 1 Petrus dengan memberikan latar teks-teks Alkitab sebagai dasar epistemologinya. Sebagai instrumen pengumpulan data menggunakan angket kepada sejumlah 50 responden Guru PAK yang mewakili 5 wilayah yakni: Jakarta Pusat, Jakarta Utara, Jakarta, Selatan, Jakarta Barat dan Jakarta Timur. Pengujian menggunakan uji regresi korelasi atas setiap butir angket dengan lima pilihan jawaban (skala Likert). Hasilnya menunjukkan, bahwa terdapat hubungan positif (searah) antara variabel Kompetensi selaku Guru PAK dengan variabel identias sebagai hamba Tuhan. Dengan nilai korelasi sebesar 0,715, maka ditunjukkan bahwa korelasi antara variabel kompetensi Guru PAK dengan identitas diri sebagai hamba Tuhan bukan hanya positif (searah) tetapi juga masuk dalam kategori kuat.